A directional-change events approach for studying financial time series - Monira Aloud; Edward Tsang; Richard Olsen; Alexandre Dupuis (Kiel Institute for the World Economy (IfW), 2011)
Financial markets witness high levels of activity at certain times, but remain calm at others. This makes the flow of physical time discontinuous. Therefore using physical time scales for studying financial time series, runs the risk of missing important activities. An alternative approach is the use of an event-based time that captures periodic activities in the market. In this paper, we use a special type of event, called a directional-change event, and show its usefulness in capturing periodic market activities. Our study confirms that the length of the price curve coastline as defined by directional-change events, turns out to be a long one.
Keywords: G10; 330; Directional-change event; intrinsic time; high-frequency finance; foreign exchange market; time-series analysis; Devisenmarkt; Zeitreihenanalyse; Event Study